Bordetella bronchiseptica peritonitis associated with continuous ambulatory peritoneal dialysis. - Byrd, L H (1981)
Bordetella bronchiseptica has rarely been reported as an opportunistic pathogen in humans. This is the first documented report of peritonitis due to B. bronchiseptica. The organism was seen on a Gram strain of peritoneal fluid and was isolated from a culture of the fluid. It was thought that the source of infection was related to the close contact of the patient with his dog. The patient was successfully treated with chloramphenicol administered intraperitoneally and intravenously.